Traffic modelling and performance evaluation in the Kotor cruise port - Kofjač, Davorin (Strojniški vestnik, 2013)
Simulation modelling of traffic in the Kotor cruise port is used for performance evaluation and optimization of the operational policy. During the summer, the traffic intensity of the cruise shipsŽ arrivals is higher than in other periods of the year. The increased traffic intensity causes congestion at anchorages, which can lead to significant dissatisfaction of the cruise ship operators and passengers. The simulation model, based on the port callingfrequency statistics and port tariff charges, is developed. First, the simulation model is validated against the real data. Second, several simulations are performed, where the scenarios of an extended main berth and of increased traffic intensity are evaluated in order to minimize congestion and to maximize revenue. Simulation results indicate significant queue reductions and a higher revenue, thus justifying the intention in the main berth extension.
Keywords: Kotor cruise port; model validation; modeliranje prometa; operational policy; operativna politika; port revenue; prihodki pristanišča; pristanišče Kotor; simulacija; simulation; traffic modelling; validacija modela